A New Reconstructive Technique for Posterior Vaginal Wall Defects, a Case Report. (24th January 2013) - Zetlitz, Elisabeth; Manook, Miriam; MacLeod, Alison; Hamilton, Stuart
Abstract Introduction Post‐partum vaginal laxity is a problem encountered by many women. More uncommon is a resulting vaginal defect. In most cases of laxity, a period of extensive physiotherapy can strengthen the pelvic muscles enough for symptoms to be minimized. However, this is not the case once there is a tissue defect. Aim To present a new reconstructive method for patients with posterior vaginal wall defects. Methods We present a case of a 38‐year‐old female who, 12 years prior to presentation, had a vaginal delivery. Due to complications during the delivery, she sustained pelvic trauma and developed a posterior vaginal wall defect. She had a sizable soft tissue defect, causing sexual, urinary, and confidence problems. Fat was harvested from the patient's abdomen and injected into the defect after more conservative treatment options were exhausted. Results The defect was corrected successfully using the minimally invasive Coleman fat grafting technique. Discussion/Conclusion This is to our knowledge the first case in the literature where a posterior vaginal defect has been corrected using Coleman fat grafting, and we believe that this treatment method may be of benefit to more patients. Zetlitz E, Manook M, MacLeod A, and Hamilton S. A new reconstructive technique for posteriorvaginal wall defects, a case report. J Sex Med 2013;10:2579–2581.